Abstracts of the 2014 CSBBCS Annual Meeting:. (Canadian Journal of Experimental Psychology / Revue Canadienne de Psychologie Expérimentale, 2014)
The article presents abstracts on experimental psychology topics which include the episodic amnesia, the flow of complex and seamless action of human behaviour, and the understanding of embodiment.